HASIL BELAJAR BIOLOGI SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN BERBASIS PENGALAMAN (EXPERIENTIAL LEARNING) - Rezeki Amaliah; Maria Goreti Marut (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This research is a classroom action research which aims to improve student learning outcomes in class XI SMA Jaya Negara Makassar, through the application of the Experiential Learning model. The research subjects were 15 students consisting of 8 males and 7 females. Data collection was carried out using learning outcomes tests and then the data obtained were analyzed descriptively qualitatively and quantitatively. The results obtained are as follows: (1) Biology learning outcomes in the first cycle are in the complete category as many as 6 people, and 9 students incomplete. With an average score of 64.53, the highest score of 80 and the lowest score of 40. (2) Biology learning outcomes in the second cycle were in the complete category as many as 12 people, and 3 students incomplete With an average score of 76.93, the highest score was 85 and the lowest was 60. (3) There was an increase in biology learning outcomes from cycle I to cycle II. The results of the study concluded that the experiential learning model could improve biology learning outcomes in class class XI SMA Jaya Negara Makassar.